Researching on the generation of ssiv gene transgenic tobacco plants using Agrobacterium tumefaciens - Thi Hong Minh, Nguyen; Le, Ngoc Thu; Nguyen, Hung Khac; Nguyen, Thom Thi; Pham, Ngoc Bich (VNU Journal of Science: Natural Sciences and Technology, 2017)
Increasing starch yield using gene technology is one of the most important research priorities and is of primary interest to scientists. Therefore, studies on the pathway of starch synthesis and decomposition in plants in general and for cassava in particular could contribute to promoting the goal of improving starch yield. In higher plants, starch synthase ( SS ) enzymes are encoded by five gene groups called GBL (granule-bound starch synthase), SSI, SSII, SSIII, and SSIV . In particular, each SS enzyme variant has different constituents and certain roles in amylopectin synthesis. In this study, ssiv gene from the KM140 cassava was isolated. Ssiv gene was inserted into pK7WG2D-35S:SSIV:T35S vector. Afterward, this new vector was transformed into tobacco plants using Agrobacterium tumefaciens . The success of transformation was checked by PCR and evaluation of gene expression was performed by analyzing the starch content. The results indicated that the starch content in transgenic plants was much more higher in comparison to the control at the same growing conditions (leaves 26,9 – 67,9%, roots 6,8 – 17,6%). This research could lead to a new direction in the creation of genetically modified crops that had the potential of increasing starch accumulation.